Test of CP invariance in vector-boson fusion production of the Higgs boson in the H -> tau tau channel in proton-proton collisions at root s=13TeV with the ATLAS detector - Onofre, A. (2020)
A test of CP invariance in Higgs boson production via vector-boson fusion is performed in the H→ττdecay channel. This test uses the Optimal Observable method and is carried out using 36.1 fb−1of √s=13 TeV proton–proton collision data collected by the ATLAS experiment at the LHC. Contributions from CP-violating interactions between the Higgs boson and electroweak gauge bosons are described by an effective field theory, in which the parameter ̃dgoverns the strength of CP violation. No sign of CP violation is observed in the distributions of the Optimal Observable, and ̃dis constrained to the interval [−0.090, 0.035] at the 68% confidence level (CL), compared to an expected interval of ̃d∈[−0.035, 0.033]based upon the Standard Model prediction. No constraints can be set on ̃dat 95% CL, while an expected 95% CL interval of ̃d∈[−0.21, 0.15]for the Standard Model hypothesis was expected.